THE DEVELOPMENT OF INDONESIANDEFENSE INDUSTRY POST-COLD WAR ERA - Muhammad Arsy Ashshiddiqy (Journal of Diplomacy and International Studies, 2018)
This study aims to analyze the development of Indonesian domestic defense industry after the end ofcold war. The focus of the discussion is how to improve Indonesian militarystrength and capabilitiesthrough the development of the domestic defense industry, currently Indonesia has three potential domestic defense industries (PT. Pindad, PT. Dirgantara Indonesia, PT. PAL). In the era of cold war,the securityof the Southeast Asian region countriesare very dependent on the two super power countriesUSA and USSR, but after the end of the cold war, every country in Southeast Asia has an obligation to fight for their own security, including Indonesia. Therefore, the defense industry needs to be built through the revitalization of the defense industry. According to GFP (Global Fire Power) and other military institutions Indonesia is the strongest in Southeast Asia region. To increase its military strength Indonesiaintensely developing the capabilities of the domestic defense industry and doing a lot of defense cooperation with developed countries in the world. This military theme is very interesting to discuss